Malawi: Joint sector review assessment: Advancing mutual accountability through comprehensive, inclusive, and technically robust review and dialogue - Ministry of Agriculture and Food Security, Malawi (Government of Malawi, Ministry of Agriculture and Food Security, 2014)
Agriculture joint sector reviews (JSRs) are key instruments for supporting mutual accountability and implementing the CAADP Results Framework. Malawi has already started conducting JSR meetings, which collectively review the effectiveness of policies and institutions in the agricultural sector as well as the extent to which they are achieving their intended results and outcomes. However, there is a need to strengthen the JSR process. This study was carried out to inform this initiative by performing a technical assessment of the existing JSR process. The assessment focused on three objectives: (1) to evaluate the policy and institutional environment of the implementation of NAIPs; (2) to examine the progress made toward achieving their key target outcomes and thus create baselines for future reviews; and (3) to assess the adequacy of existing processes to effectively carry out such reviews in the future and to identify actions to remedy any weaknesses seen. Some interesting findings were obtained from this assessment.